Frühe Flexibilisierung? Regionale Mobilität nach der Lehrausbildung in Deutschland zwischen 1977 und 2004 - Holger Seibert (Institut für Arbeitsmarkt- und Berufsforschung (IAB), 2007)
This paper examines if and to what extend regional mobility has increased after finishing vocational in-firm training between 1977 and 2004. Particular interest is given to the importance of regional mobility for occupational continuity at labor market entry. Can mobility lower the probability of occupational shifts so that human capital investments are not written off early? Can regional mobility in this sense be used as a strategy to optimize labor market opportunities and has it become more important over time? Analyses show that regional mobility can indeed be used strategically to find jobs in the occupation trained for. Its importance, however, is limited and has not changed over time significantly. Nevertheless, mobility improves the fit between actual occupation and the one trained for.
Keywords: J62; 330; regionale Mobilität; Berufsausbildung; Ausbildungsabsolventen; Berufseinmündung; Berufswechsel; Arbeitsmarktchancen; Ausbildungsberufe; zweite Schwelle; Berufseinstieg; Jugendliche Arbeitskräfte; Regionale Arbeitsmobilität; Erwerbsstatus; Deutschland